Beneficios de toxina botulínica en el tratamiento fisioterapéutico de la parálisis cerebral infantil - Karla Micaela, Robles Bustos (2021)
ABSTRACT The research focused on the modality of bibliographic review, revealing the benefits of botulinum toxin in the physiotherapeutic treatment of infantile cerebral palsy, determining the contribution provided by the administration of BoNT for the rehabilitation treatment seeking to improve the quality of life of pediatric cerebral palsy patients to provide new, safe and effective treatment protocols for their speedy recovery. Botulinum toxin in children with infantile cerebral palsy is not widely used in the workplace, due to the lack of bibliographic material provided online, despite this, 80 scientific articles found with one or both variables referring to the main topic, in mostly from bibliographic sources such as: Physiotherapy Magazines, Neurology, Google Scholar Scielo, PubMed and El Sevier. According to the established exclusion criteria and evaluation of the articles on the PEDro scale, 35 articles considered suitable for the study, since they met a score equal to or greater than 6 on the PEDro scale of which found in different languages translated into Spanish. At the end of the research, it was possible to complete the proposed objective, to identify the benefits of botulinum toxin in the physiotherapeutic treatment of infantile cerebral palsy. Key words: Infant cerebral palsy, cerebral palsy, botulinum toxin, botulinum toxin type A, PCI, BoNT-A. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324